Evaluación Antimicrobiana y Fitoquímica de Lepechinia Meyeni Walp "Salvia" - Rossi, Cesar (2002)
The antimicrobial activity of the methanol and water extracts of Lepechinia meyeni. Walp was evaluated. The methanol extract showed antimicrobial activity for gram positives bacterias also for Salmonella enteritidis y Shigella flexneri. Phytochemical screening the presence of flavonoid, phenolic compounds, tannins, terpenoids and steroids was determine.